IN SILICO POTENTIAL ANALYSIS OF X6D MODEL OF PEPTIDE SURFACTANT FOR ENHANCED OIL RECOVERY - Cut Nanda Sari; Usman Usman; Rukman Hertadi; Tegar Nurwahyu Wijaya; Leni Herlina; Ken Sawitri Suliandari; Syafrizal Syafrizal; Onie Kristiawan (Scientific Contributions Oil and Gas, 2016)
Peptides and their derivatives can be applied in enhanced oil recovery (EOR) due to their ability to form an emulsion with hydrophobic molecules. However, peptide research for EOR application, either theoretical or computational studies, is still limited. The purpose of this research is to analyse the potency of the X6D model of surfactant peptide for EOR by molecular dynamics simulations in oil-water interface. Molecular dynamics simulation using GROMACS Software with Martini force field can assess a peptide’s ability for self-assembly and emulsification on a microscopic scale. Molecular dynamics simulations combined with coarse grained models will give information about the dynamics of peptide molecules in oil-water interface and the calculation of interfacial tension value. Four designs of X6D model: F6D, L6D, V6D, and I6D are simulated on the oil-water interface. The value of interfacial tension from simulation show the trend of F6D L6D > I6D > V6D. The results indicate that V6D has the greatest reduction in interfacial tension and has the stability until 90°C with the salinity of at least 1M NaCl.